Regulatory Obligations Of The Electronic Communications Market, Administrative And Judicial Appeal, And Monitoring: Inspection And Sanctions In Albania - Gjika, Jonida (European Scientific Journal, ESJ, 2016)
Electronic communications services and the dynamics of their development require in itself special care and continuous efforts of the national policies. This is used to build effective strategies with the aim of laying the right steps. It is in coherence with international development of the electronic communications market for the products. It also serves as an integral part of its services. Some of the decision which will result to measurable effects in the market include: concrete steps which are related to the harmonization and alignment of the full legislation national primary, absorption and outline of the directives of the EU as an integral part thereof, drafting regulatory acts as secondary legislation, and continuous care for a hand regulatory which is strong and neutral. For careful coordination of the chains as a whole in the chain functioning of this market, where policies and sectoral strategies, regulatory and decisionmaking, entrepreneurs and consumers in the market of products/services offered are on the side of maximum benefits, it would first of all mean finding the appropriate instruments and implement them in a legal manner. This is possible through effective remedies. Thus, the development of competition is the only way that would make it possible for all the actors to find themselves on the side of the party that would win.